Corporate Governance of Islamic Banks, Earning Management and Firms Value: A Conceptual Framework - Puspita, Harsono Edwin (Dirham: Journal of Sharia Finance and Economics, 2025)
Purpose: This study examines the role of corporate governance in mitigating earnings management and its impact on firm value in Islamic banking institutions, emphasizing the function of Sharia Supervisory Boards within a dual governance framework. Research Methodology: A quantitative panel data approach is employed using observations from Islamic banks over multiple periods. Corporate governance is proxied by board characteristics, ownership structure, audit committee attributes, and Sharia Supervisory Boards. Earnings management is measured using discretionary accrual-based models, while firm value is captured through market-based valuation indicators. Panel regression techniques are applied to analyze direct and indirect relationships among variables Results: The results indicate that stronger corporate governance mechanisms are associated with lower levels of earnings management, suggesting effective monitoring of managerial discretion. Earnings management is found to negatively affect firm value, implying that capital markets penalize opportunistic financial reporting. Several governance attributes also demonstrate a direct positive relationship with firm value by enhancing transparency and investor confidence. Conclusions: The study confirms that robust corporate governance, particularly Sharia-based oversight, plays a vital role in constraining earnings management and improving firm value in Islamic banks, supporting agency and signaling theories. Limitations: This study relies on accrual-based earnings management measures and secondary governance data, which may not fully capture real activity manipulation Contribution: This research contributes to Islamic finance literature by empirically clarifying the governance–earnings management–firm value nexus and offers practical insights for regulators and practitioners to strengthen governance frameworks in Islamic banking.